If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 12 = 10x + -10 Reorder the terms: 12 + 12x = 10x + -10 Reorder the terms: 12 + 12x = -10 + 10x Solving 12 + 12x = -10 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 12 + 12x + -10x = -10 + 10x + -10x Combine like terms: 12x + -10x = 2x 12 + 2x = -10 + 10x + -10x Combine like terms: 10x + -10x = 0 12 + 2x = -10 + 0 12 + 2x = -10 Add '-12' to each side of the equation. 12 + -12 + 2x = -10 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = -10 + -12 2x = -10 + -12 Combine like terms: -10 + -12 = -22 2x = -22 Divide each side by '2'. x = -11 Simplifying x = -11
| 0.86=In(y) | | 3/7x-4=12 | | 3/7x-4=16 | | 3x+18x^2-81x=0 | | -4(x-1)=10x-10 | | 4x-14/x-3 | | Y=80-2x | | 4v+28=v+51 | | 3x+7=7x+13 | | 3tgx+4=tgx+4 | | 18/x-3=6 | | 2x^2+6=166 | | 15x^2-2=123 | | 2w=10w-32 | | 7x-11=5x-15 | | 90=-6+2(-4x+10) | | 0=2x^2-6x+24 | | V+8=-3 | | h(t)=-5t^2+80t+3 | | 7x+9=-3y | | 5x^2-2=123 | | 15-10*4= | | 3x+7+3y-1=180 | | ×/4=3.6 | | -2b+3b=19 | | 3(2x+5)=8x+3 | | 0.044x=200 | | X+8x+90=180 | | 25p-5=5 | | 2(x+1)+5=-7(x+1)-13 | | 4/=3.6 | | 45=9(5c+12) |